Spain : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2007)
This report examines the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Spain. The findings reveal that the Spanish legal framework for combating money laundering and terrorist financing is generally comprehensive. Money laundering offences are broad in scope and easy to apply, according to Spanish prosecutors. Terrorist financing offences are broadly satisfactory, although they do not appear to cover acts of an individual terrorist and collection of funds under certain circumstances.